Production of biosurfactant by Lysinibacillus sp. and Bacillus sp. from different oils as carbon source - Mendes de Almeida, Grazieny Aparecida; Araujo Vieira Neta, Maria dos Remedios; Silva, Gabriela Fiori da; Prado, Pierre Ferreira do [UNESP]; Almeida, Monica Aparecida de; Silveira Duarte, Iolanda Cristina (Univ Fed Rio De Janeiro, Lab Hidrogenio, 2020)
Biosurfactants are multifunctional molecules produced by microorganisms and have some advantages compared to synthetic surfactants, such as low toxicity, high biodegradability ,improved tensoactivity and chemical diversity. However, commercial scale production is not viable due to the high cost of the substrates used. Therefore, in the present work we evaluated the production of biosurfactants using different oils as carbon source, such as soybean oil, frying oil, diesel oil, new and used lubricating oil, from two genera of bacteria isolated from sludge cosmetics industry and soil contaminated with diesel oil, Lysinibacillus sp. and Bacillus sp. respectively. These were identified by sequencing the 16S rRNA gene fragment and kept under refrigeration at 4 degrees C in test tubes with tryptone soy agar. The production was carried out under agitation at 200 rpm at 30 degrees C for 7 days. The biosurfactant production was analyzed by emulsifying activity, emulsification index and drop collapse. The bacteria used produced biosurfactant in all types of oils tested. Soybean oil was the best substrate for the production of biosurfactant from Lysinibacillus sp. and Bacillus sp. with an emulsification index of 50% and 46.63%, respectively.
Keywords: Emulsifiers; bacterium; alternative sources; fermentation